Isolation and characterization of cellulose nanocrystals from parenchyma and vascular bundle of oil palm trunk ( Elaeis guineensis ) - Junidah, Lamaming; Rokiah, Hashim; Leh, Cheu Peng; Othman, Sulaiman; Tomoko, Sugimoto; Mohammed, Nasir (Elsevier Ltd., 2015)
n this study cellulose nanocrystals were isolated through acid hydrolysis process from parenchyma and vascular bundle of oil palm trunk (Elaeis guineensis). The morphological properties of obtained cellulose nanocrystals were studied by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The microscopy images showed smoother and cleaner surface of parenchyma cellulose nanocrystals when compared to vascular bundle cellulose nanocrystals. The TEM image shows a higher length and diameter for parenchyma cellulose nanocrystals compared to vascular bundle cellulose nanocrystals. The Fourier transform infrared (FTIR) spectra showed changes in functional groups after acid hydrolysis due to removal of lignin, hemicelluloses and other impurities in both type of cellulose nanocrystals. Crystallinity index of cellulose nanocrystals was observed higher for vascular bundle as compared to parenchyma. Thermogravimetric analysis (TGA) was performed to study the thermal stability of cellulose nanocrystals and it was observed higher for parenchyma cellulose nanocrystals compared to vascular bundle.